URDU-AN INTRODUCTORY AND ANALYTICAL STUDY OF URDU LITERATURE ON THE MIRACLES OF THE PROPHET IN PAKISTAN - Asma Aziz; Arif Mateen (دی اسکالر)
Being something stupendously out of the ordinary and something that defies all worldly laws, a miracle has always drawn the attention of people in various religions. According to Islam, miracles are performed with the permission of God to prove the prophecy of messengers who were primarily sent to guide humankind. Prophet Muhammad (SAW) was also supported with many miracles including Quran, splitting the moon, night journey, ascension to the heavens, tree trunk, the flowing of water blessing of food, and many more. A large number of books covering the various aspects of miracles performed by Prophet Muhammad (PBUH) have been produced in the Urdu language. In addition to exploring the meaning, scope, and results, the authors have also examined the narrations and their authenticity pertinent to miracles.  This article aims to present an introductory review of such books including their titles, authors, year of publication, publishers, and number of pages. Furthermore, a summary of the content of the books, the methodology adopted by the authors, some examples as well as analysis and critical evaluation are also highlighted in this study where needed. This humble effort will facilitate the reader to select a book of one’s choice after reading this brief description on one hand. On the other, it will also help the researchers and experts in their detailed study and further their deeper understanding of the topic.